“Contrecoup” Paravalvular Leak Closure - Agbor-Etang, Brian B.; Rao, Ravi M.; Mukherjee, Ashis; Sethi, Prabhdeep S.; Pai, Ramdas G. (International Journal of Angiology, 2019)
Paravalvular aortic regurgitation affects some patients after surgically implanted prosthesis. The number of patients affected is likely to increase with increased utilization of nonsurgical valve replacement techniques. These patients are at increased risk of persistent clinical symptoms often requiring repair. Clinical and procedural outcomes are of importance when performing these procedures and managing these patients. We describe a case where two different leaks around an aortic prosthesis improved with closure of one defect.
Keywords: aortic valve; closure; leak; paravalvular; regurgitation; prosthetic; amplatzer